Restructuring for relevance: a paradigm shift for academic libraries. Issue 6 (13th August 2018) - Raju, Reggie; Claassen, Jill; Adam, Amina; DAngelo, Alexander; Keraan, Sadiq; Mostert, Niel; Vonk, Saskia
Abstract : Purpose: The purpose of this paper is to report on the development of a flexible and robust academic library structure that meets the demands of an ever changing user community and remains relevant and fit for purpose in a technology-driven age. The new structure makes provision for the delivery of new and innovative services responding to the need for a paradigm shift in twenty-first century academic librarianship. The move away from subject librarianship, which has been the bastion of South African academic librarianship, is significant. Design/methodology/approach: This paper used the exploratory method to gain new insights into library structures that have restructured for the twenty-first century. The exploratory study was used to gain new insights into functional librarianship. Despite the short comings of the exploratory method, the method was deemed most appropriate as UCT Libraries was not seeking definitive answers but a process that would provide opportunities to explore possibilities for subsequent processes. Findings: The move from subject librarianship to functional librarianship has given the library the opportunity to restructure. The restructured library can now offer new and/or radically expanded services to meet the demands of a twenty-first century academic library. Practical implications: The development of new and future roles and responsibilities commensurate with a robust and "future-driven" structure will consolidate the library's role as a collaborator in the teaching and learning, and research agendas of a higher education institution. Originality/value: This paper will be of interest and value to library managers and staff wanting to develop a library structure that responds positively to the redefinition of the professional roles and functions of the library and to strategically position the academic library for the future. It will also be of interest to library and information science academics who may want to re-examine their curricula for the incorporation of new trends.